SISTEM INFORMASI SOSIALISASI DAN PROMOSI BERBASIS WEB PADA STMIK NURDIN HAMZAH JAMBI: Data Socialization and Promotion, MySQL, PHP, Socialization and Promotion, STMIK Nurdin Hamzah, Web. - Simorangkir, Lucy; Furnawan, Hambali; Zainul Arifin, M. (JURNAL AKADEMIKA, 2019)
The Nurdin Hamzah Jambi School of Information and Computer Management (STMIK) is one of the computer science colleges established in 1992. During this time the data processing of the socialization and promotion of the Nurdin Hamzah Jambi STMIK is still done manually, that is, the socialization and promotion data processing is recorded on paper, and using Microsoft Word and Microsoft Excel software so that the data collection and analysis of information dissemination and promotion process takes a very long time, data errors often occur and data searches are not so fast. The purpose of this research is to build an information system application that can later be used also as a means to process data dissemination and promotion. In making the Executive Information System for Socialization and Promotion used the PHP programming language. As well as using the Database using MYSQL. With the information system of the Executive Socialization and Promotion that was built, it made it easier for the staff of the socialization and promotion of STMIK Nurdin Hamzah Jambi to process the socialization and promotion data effectively and efficiently. By inputting the data of the promotion team, school socialization, school actualization, schedule and budget so as to produce output in the form of a report on the promotion team, school socialization, school actualization, schedule and budget. The existence of the Executive Information System for Socialization and Promotion is expected to improve the performance of the socialization and promotion team at STMIK Nurdin Hamzah Jambi.